Comparing two psychological interventions in reducing impulsive processes of eating behaviour: Effects on self‐selected portion size. (21st October 2013) - van Koningsbruggen, Guido M.; Veling, Harm; Stroebe, Wolfgang; Aarts, Henk
<x xml:space="preserve">Abstract</x> Objective Palatable food, such as sweets, contains properties that automatically trigger the impulse to consume it even when people have goals or intentions to refrain from consuming such food. We compared the effectiveness of two interventions in reducing the portion size of palatable food that people select for themselves. Specifically, the use of dieting implementation intentions that reduce behaviour towards palatable food via top‐down implementation of a dieting goal was pitted against a stop‐signal training that changes the impulse‐evoking quality of palatable food from bottom‐up. Design We compared the two interventions using a 2 × 2 factorial design. Methods Participants completed a stop‐signal training in which they learned to withhold a behavioural response upon presentation of tempting sweets (vs. control condition) and formed implementation intentions to diet (vs. control condition). Selected portion size was measured in a sweet‐shop‐like environment (Experiment 1) and through a computerized snack dispenser (Experiment 2). Results Both interventions reduced the amount of sweets selected in the sweet shop environment (Experiment 1) and the snack dispenser (Experiment 2). On average, participants receiving an intervention selected 36% (Experiment 1) and 51% (Experiment 2) fewer sweets than control participants. In both studies, combining the interventions did not lead to additive effects: Employing one of the interventions appears to successfully eliminate instrumental behaviour towards tempting food, making the other intervention redundant. Conclusions Both interventions reduce self‐selected portion size, which is considered a major contributor to the current obesity epidemic. Statement of contribution What is already known on this subject? Exposure to temptations, such as unhealthy palatable food, often frustrates people's attainment of long‐term health goals. Current approaches to self‐control suggest that this is partly because temptations automatically trigger impulsive or hedonic processes that override the influence of more deliberate processes on behaviour. This perspective has stimulated the development of new interventions – which have so far been studied in isolation – aimed at decreasing the influence of impulsive or hedonic processes to decrease unhealthy eating behaviour. What does this study add? Linking sweets to stop signals and diet‐prime implementation intentions both reduce self‐selected portion size. Combining the interventions does not lead to additive effects. Each intervention reduces self‐selected portion size of sweets, making the other redundant.